An audit of emergency response to terrorist-related bomb blasts and gunshot injuries - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:The management of mass casualty events caused by terrorist-related suicide bombings in densely populated areas is often challenging.Aims:This study describes the pattern of injuries, the emergency response following a suicide bombing in Nigeria in 2014 and compares the outcomes to those of other incidents.Settings and Design:A retrospective analysis of cases that presented to a major tertiary care center was done.Methods and Material:Medical records of 50 patients who experienced bomb blast or gunshot wounds during 28thNovember, 2014 suicide bombing of the Kano Central Mosque were reviewed and 12 eyewitnesses were interviewed.Statistical analysis used:Descriptive analysis of quantitative data was done while major themes were identified from the key informant interviews.Results:Fifty patients were admitted at the acute care center within 4 hours. There was a male predilection (98%), with a median age of 30 years (IQR, interquartile range = 37.5 years). Most injuries were the result of multiple penetrating projectiles (secondary blast injuries), primarily involving blast-energized metallic fragments like screws, nails, bolts, ball bearings, and metal scraps. Eleven patients (22%) had minor lacerations, about a quarter (n= 12; 24%) had severe hemorrhage and were transfused, five (10%) had multi-system involvement, and mortality rate was 8% (n= 4). Interventions were aimed at preserving the lives of those injured.Conclusion:Most of the victims had major injuries which were appropriately managed although the hospital lacked an existing protocol on mass casualty management. Increased awareness, organized field triage mechanisms, and capacity building in health facilities will facilitate prompt emergency response.